A Study on the Relationship between Organizational Commitment, Position Promotion, and Work Discipline with Employee Performance at the North Labuhanbatu Regency Education Office - Ismail, Ismail; Sugiani, Susi; Siahaan, Songgy Meiner; Wulandari, Wulandari; Chairul, Rachmawati; Suprayitno, Eddi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the relationship between organizational commitment, job promotion, and work discipline on employee performance at the North Labuhanbatu Regency Education Office. A quantitative survey method was employed, with questionnaires distributed to 108 employees. The data were analyzed using multiple linear regression. The findings revealed that all three variables significantly impact employee performance, with work discipline being the most influential factor. The coefficient of determination (R²) of 58.2% indicates that these three variables explain a substantial portion of the variation in employee performance. Based on these results, the study recommends enhancing work discipline, reinforcing organizational commitment, and improving the transparency of job promotions to boost employee performance.